2011
DOI: 10.1103/physreve.83.041911
|View full text |Cite
|
Sign up to set email alerts
|

Postfragmentation density function for bacterial aggregates in laminar flow

Abstract: The postfragmentation probability density of daughter flocs is one of the least well-understood aspects of modeling flocculation. We use three-dimensional positional data of Klebsiella pneumoniae bacterial flocs in suspension and the knowledge of hydrodynamic properties of a laminar flow field to construct a probability density function of floc volumes after a fragmentation event. We provide computational results which predict that the primary fragmentation mechanism for large flocs is erosion. The postfragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…In particular, we are interested in the propensity of suspended bacterial aggregates to fragment in a flowing system. The model proposed in [29] uses knowledge of the hydrodynamics to predict a breakage event and thus the post fragmentation density Γ. With this work, we now have a tool to bridge the gap between the experimental and microscale modeling efforts for fragmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we are interested in the propensity of suspended bacterial aggregates to fragment in a flowing system. The model proposed in [29] uses knowledge of the hydrodynamics to predict a breakage event and thus the post fragmentation density Γ. With this work, we now have a tool to bridge the gap between the experimental and microscale modeling efforts for fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In [29], we found that the resulting post-fragmentation density for small parent flocs resembles a Beta distribution with α = β = 2 (see Figure 1a for an illustration). Therefore, the first artificial data set was generated from the forward problem by assuming model rates given in (22)–(23) and a post-fragmentation density function a Beta distribution with α = β = 2, Γtruefalse(x,yfalse)=𝟙false[0,yfalse]false(xfalse)6xfalse(yxfalse)y3. As in Section 4.1, we chose exponential initial size-distribution b 0 ( x ) = 10 3 exp( x ) on Q = [0, 1] for t f = 10.…”
Section: Application To Flocculation Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the biofilm is not attached to the plates and is sufficiently far from the plate to induce a rotating, or tumbling motion, these simulations only include bacteria that are greater than 8.8 µm from either plate at the start. With the physical parameters we use, the bacteria aggregation rotates and is deformed by the fluid shear forces exerted by the fluid [6]. In Blaser et al [3], analytical results on the frequency at which a solid ellipsoid will rotate in shear flow are provided.…”
Section: Similarity Of Materials Properties Between Different Bacteriamentioning
confidence: 99%
“…The present study is geared towards tracking the size distribution of spherical floc aggregates in stagnant fluid conditions [29]. The spherical particles within the flocs adhere through well-defined disc-like patches covered with binding ligands.…”
Section: Mathematical Model: Binder Kinetics Effect Of Surface Chamentioning
confidence: 99%